Aging, sexual intimacy, and challenges in contemporary India: A qualitative study - Srivastava, Sanchita; Upadhaya, Puja (Frontiers in Psychology, 2022)
An individual's life is shaped by age norms practiced in a particular society. In most societies, there is a deadline for every life event. Sexual intimacy is an essential part of every individual. However, sexual intimacy seems appropriate for young individuals, and middle-aged and older are considered asexual. Those who share sexual intimacy at a later age have to face the consequences for this age-inappropriate behavior in society. This study analyses “Badhaai Ho” film to explore the consequences of sharing sexual intimacy by middle-aged heterosexual couples in their 50s as it is forbidden by prevalent social norms. This study also explores the role of family in dealing with the repercussions of actions against the prescribed social norms. Thematic analysis suggests that society has a predefined age-bound box for individuals with different age categories. The middle-aged couple suffers various consequences for breaking the prescribed age-bound box. The role of the family is found to be crucial in mending the box by replacing it with an updated version. There are also gender differences in attitude toward sexual intimacy. Implications of this study can be utilized to explore the pathway of social change in existing social (age) norms in any society.